Manajemen Pengarsipan pada Biro Umum Sekretariat Daerah Provinsi Jawa Timur - Silalahi, Clara Monika; Bataha, Katerina (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2024)
Archives serve as a repository of invaluable information crucial to the organizational sustainability process, capturing diverse historical aspects. The primary objective of archive management is to systematically organize, store, and facilitate access to this information, catering to researchers, historians, scholars, and individuals interested in the study of specific subjects or periods. This research adopts a qualitative descriptive methodology, utilizing observations, documentation, and interviews for data collection. The collected data is then systematically organized and expounded upon using a descriptive approach, providing insights into archival management within the General Bureau of the Provincial Secretariat of East Java. The Sub-Section of Correspondence and Archives within the General Bureau of the Provincial Secretariat of East Java is identified as a key department responsible for archival functions. Notably, archival management in this bureau adheres to the principle of decentralization, granting each section within the General Bureau, including the Household Section, Financial and Asset Administration Section, and Administrative Affairs Section, the autonomy to manage archives independently. The findings of this research affirm that archival management in the General Bureau of the Provincial Secretariat of East Java aligns with the five key aspects of archive management, encompassing the recording of incoming and outgoing correspondence, archival storage, maintenance, depreciation, and disposal of archives. The archival management processes within the General Bureau of the Provincial Secretariat of East Java operate optimally, supported by the availability of adequate human resources and electronic applications. Keywords: management, archive